DAMPAK PEMBANGUNAN JALUR JALAN LINTAS SELATAN (JJLS) TERHADAP PERUBAHAN PENGGUNAAN LAHAN DI DESA GADINGSARI, KECAMATAN SANDEN, KABUPATEN BANTUL, YOGYAKARTA - Edy, Hendry; Baiquni, M.; Triatmodjo, Bambang (Jurnal Spasial, 2019)
Infrastructure Development Jalur Jalan Lintas Selatan (JJLS) is a National program that passes through 5 provinces in Java, which is one of the provinces passed through the Special Region of Yogyakarta. One of the villages passed by the JJLS development in the Special Province of Yogyakarta is Gadingsari Village, Sanden District, Bantul Regency. In this study, it will be seen how changes in land use in Gadingsari village before and after JJLS. The purpose of this study was to analyze changes in land use that occurred in Gadingsari Village. The analytical method used is a qualitative descriptive analysis method. Changes in land use were obtained from the Satellite Image Overlay Analysis in the span of time, namely before JJLS was built in 2013 and after JJLS was built in 2017 and strengthened with field surveys and in-depth interviews. From the results of the research, it was found that the land area for settlements in Gadingsari Village before and after the JJLS had changed. Before the existence of JJLS residential area was 78.90 hectar and it expanded to 104.93 hectar after the construction of JJLS, there was an increase of around 32.99% .